Profil Kadar Lemak dan Berat Jenis Susu Sapi Peranakan Friesien Holstein di KUD Kertajaya Kandangan, Kediri yang Diberikan Pakan Rumput Odot (Pennisetum purpureum) dan Konsentrat A18: Profile of Fat and Density in Friesien Holstein Cow’s Milk t KUD Kertajaya Fed with Odot Grass (Pennisetuma purpureum) and A18 Concentrate - Prasetyo, Dodik; Herawati, Herawati; Yessica, Reza; Yulia, Eka (Jurnal Riset Agribisnis dan Peternakan, 2023)
The quality of feed will affect the quality of produced milk. The higher the nutrient feed, make the quality of the milk better. Medowo Village is one of the centers for dairy farming in Kediri that were fed with odot grass and A18aconcentrate. This research is adescriptive observational study which aims to describe the profile of milk quality iSn terms of fat rate and density in Friesien Holstein crossbreed cow’s milk that were fed with odot grass and A18 concentrate. The sample was collected using purposive sampling technique and then the total of minimum sample are calculated using the systemic sampling formula with 20 dairycows’s sample. The collected data of milk quality are analyzed using descriptive and correlation in the Pearson test to determine the strength of relation between the independent variable and the dependent variable. The results showed that the average fat rate of Friesien Holstein Crossbreed cow’s milk in KUD Kertajaya was 4.8% (equal to 0.192) with an average density of 1.0246 g/ml (equal to 0.001). There was a significant positive correlation (P<0.05) between the quality of nutrient in odot grass ration and A18 concentrate with the quality of milk fat and density of milk